Synthesis of Semliki Forest virus RNA polymerase components nsP1 through nsP4 in Saccharomyces cerevisiae by expression of cDNA encoding the nonstructural polyprotein. - Russo, P (1996)
A Semliki Forest virus nonstructural polyprotein, P1234, expressed in the yeast Saccharomyces cerevisiae in the absence of a replicative RNA template appeared to be properly cleaved into nsP1 to nsP4. All nsPs were membrane associated, and nsP2 was also transported to the nucleus. The membrane fraction containing nsPs showed guanine-7-methyltransferase and guanylyltransferase-like activities, typical for Semliki Forest virus nsP1.